Identifikasi Teknik Data Mining Metode Asosiasi: Systematic Literature Review - Lutfina, Erba; Yuanita, Syafira Putri; Dimentieva, Imelda; Pribadi, Ahmad Naufal; Syahidan, Mukhammad Shaunan; Safa’at, Mochammad Alief Fauzan Akbar; Loekito, Joseph (Science Technology and Management Journal, 2024)
Data mining is a process of collecting important information from large data. Data mining has many functions, one of which is the description function. In this case, the description function is that later data mining can find certain patterns hidden in data. This research aims to identify which association methods in data mining are most often used, identify the most dominant dataset models in association methods, identify the most relevant journal years in association methods, identify what fields most often use association methods, and find out the objectives of researchers using association methods such as FP-Growth and Apriori in various related journals. Using a Systematic Literature Review (SLR) approach, to answer the research questions that have been prepared from the analysis with a total of 33 related journals. So as a result, this study shows that the application of the SLR method can provide answers to the research questions that have been prepared.